2017
DOI: 10.1002/mus.25601
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in muscle strength with low‐load isotonic training depends on fascicle length but not joint angle

Abstract: Introduction: In this study we investigate whether low-load isotonic training will elicit greater improvement in muscle strength at the same fascicle length, rather than at the same joint angle. Methods: Sixteen healthy men (24.1 6 2.5 years of age) were randomly divided into intervention and control groups. Pre-and posttraining maximum isometric and isokinetic strengths and fascicle lengths of the medial gastrocnemius muscle were measured. Isotonic resistance training at 15 8 to 30 8 ankle plantarflexion at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
1
7
0
1
Order By: Relevance
“…The results of the present study did not follow the principle of specificity of joint angle, which was proposed by Kitai and Sale 5) and widely accepted [10][11][12] . On the other hand, the results supported the previous studies 7,8) , which reported that the MVC was improved more at an agonist muscle lengthened position than at the same position using training.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of the present study did not follow the principle of specificity of joint angle, which was proposed by Kitai and Sale 5) and widely accepted [10][11][12] . On the other hand, the results supported the previous studies 7,8) , which reported that the MVC was improved more at an agonist muscle lengthened position than at the same position using training.…”
Section: Discussionsupporting
confidence: 90%
“…Kitai and Sale (1989) 5) reported that ankle plantarflexion training with a high load improved in the MVC at an ankle position only used during training. The previous study addressed this issue and found that low-load training at the agonist muscle in the shortened position improved the muscle strength only at a more lengthened (dorsiflexion) position than the position used during training in healthy young men 7,8) . Regarding the results, the authors also reported that the fascicle length during the training position, measured using ultrasound, was similar to the fascicle length during maximum voluntary contraction (MVC) at the angle that was obtained during improvements in MVC.…”
mentioning
confidence: 99%
“…The data were nonnormally distributed and, therefore, log-transformed when analyzed and are presented as means Ϯ SD of raw data. no change (51,64,69,72) or only increases in FL (73) or PA (27,30,60). Based on previous studies (49,74), a greater FL increase induced by training is suggested to occur when training is performed at long MTU lengths due to a longer muscle stretch.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, a clinical trial of 61 patients with KOA showed that isotonic exercise can alleviate pain, stiffness, and improve knee joint function effectively, but it cannot increase quadriceps strength significantly ( Malas et al, 2013 ). In addition, Tanaka et al (2018) found that the muscle strength of patients with KOA could be effectively improved through low-load isotonic resistance exercise. Moreover, isotonic-centripetal exercise and isotonic-eccentric exercise has the same effect on increasing knee extension and knee flexion muscle strength, as well as relieving pain in patients with KOA ( Vincent et al, 2019 ).…”
Section: Exercise Training and Koamentioning
confidence: 99%